APOE genotype and brain amyloid are associated with changes in the plasma proteome in elderly subjects without dementia - Philippi, Sarah M.; BP, Kailash; Raj, Towfique; Castellano, Joseph M. (Annals of clinical and translational neurology, 2025)
Objective Recent work has bolstered the possibility that peripheral changes may be relevant to Alzheimer's disease pathogenesis in the brain. While age‐associated blood‐borne proteins have been targeted to restore function to the aged brain, it remains unclear whether other dysfunctional systemic states can be exploited for similar benefits. Here, we investigate whether APOE allelic variation or presence of brain amyloid are associated with plasma proteomic changes and the molecular processes associated with these changes. Methods Using the SOMAscan assay, we measured 1305 plasma proteins from 53 homozygous, APOE3 and APOE4 subjects without dementia. We investigated the relationship of either the APOE‐ε4 allele or amyloid positivity with plasma proteome changes by linear mixed effects modeling and ontology‐based pathway and module–trait correlation analyses. Results APOE4 is associated with plasma protein differences linked to atherosclerosis, tyrosine kinase activity, cholesterol transport, extracellular matrix, and synaptogenesis pathways. Independent of APOE4, we found that subjects likely harboring brain amyloid exhibit plasma proteome signatures associated with AD‐linked pathways, including neurovascular dysfunction. Interpretation Our results indicate that APOE4 status or presence of brain amyloid are associated with plasma proteomic shifts prior to the onset of symptoms, suggesting that systemic pathways in certain risk contexts may be plausible targets for disease modification.